Water quality and the impact to the health - Diana Sunardi (Indonesian Nutrition Association, 2022)
Water is the major constituent of the human body. Water is essential for life and maintaining optimal levels of hydration is important for humans to function well. Water makes up a large proportion of our body weight, distributed between the intracellular (inside cells) and extracellular (water in the blood and in between cells) compartments. Water is the major component of body ﬂuids, such as blood, synovial ﬂuid (ﬂuid in the joints), saliva and urine, which perform vital functions in the body. Human body cannot produce enough water by metabolism or obtain enough water by food ingestion to fulfil its needs. As a consequence, we need to pay attention to what we drink throughout the day to ensure that we are meeting our daily water needs, as not doing so may have negative health effects.